National School Food Program in the context of federalism: Under the gaze of the educational manager - Rosaria Cal Bastos; Magnus Luiz Emmendoerfer; Amélia Carla Sobrinho Bifano; Maria das Dores Saraiva Loreto (Arizona State University, 2019)
This article assumes that the local level managers of the National School Food Program (PNAE) faces challenges shaded by the organizational form of the State in Brazil at the time of the implementation of this policy. In this sense, the central objective is to analyze the aspects of federalism in the PNAE, drawing reflections for the educational managers on the process of PNAE implementation coordinated by the Union and its effects on intergovernmental relations. In addition, it is also showed the challenges faced by PNAE managers at the local level. In methodological terms, a case study, based on documents and interviews with semi-structured scripts, was applied to the PNAE managers, municipal and state, in the city of Coimbra, MG. The results indicated the differences in the guidelines and goals established in the PNAE planning at the local level due to the non-integrated performance of two federative entities, which generate difficulties for educational managers in terms of PNAE management. Therefore, considering the particularities of federalism in the context of the PNAE may bring new perspectives to this program to be an educational instrument that interconnects healthy eating and the nuances of the local culture, redesigning its formulation and implementation process, aiming to provide a better performance of public management, especially, toward schooling.